2006
DOI: 10.1258/135763306776738594
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to the use of videoconferencing in general and specialist psychiatric services

Abstract: Mental health professionals and support staff were invited to complete a questionnaire about their experience of using videoconferencing. Our hypotheses were that mental health professionals in the UK do not have access to videoconferencing and do not believe that videoconferencing is appropriate for their work. Of the 134 people who completed and returned a questionnaire, 78 worked in deaf mental health services and 56 worked in general mental health services. The majority were nurses (n = 33) or psychologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Although therapists using VC sometimes rated TA at a lower level than clients, in general their TA ratings ranged from moderate to very high. The evidence also suggests that even psychologists with little experience in video therapy usually become accustomed to it in a relatively short period of time . Several factors have been identified as crucial in terms of the capacity of the therapist to facilitate TA in the context of in‐person therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Although therapists using VC sometimes rated TA at a lower level than clients, in general their TA ratings ranged from moderate to very high. The evidence also suggests that even psychologists with little experience in video therapy usually become accustomed to it in a relatively short period of time . Several factors have been identified as crucial in terms of the capacity of the therapist to facilitate TA in the context of in‐person therapy.…”
Section: Resultsmentioning
confidence: 99%
“…However, some reported that the portal requires advanced IT skills, although the nurses in our study received extra individual education for portal use and technical support was daily available. The problems in using IT may be explained by their IT skills (Lorenzi & Riley 2000), lack of time (McLane 2005) or negative attitudes and fears to computers (Austen & McGrath 2006). The majority of respondents were women and nearly half of them were also over 50 years old.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure usability at an early stage of the development process (Tod et al . 2003, Davis & Venkatesh 2004, Gosling et al .…”
Section: Introductionmentioning
confidence: 99%
“…There are more barriers from the clinicians' perspective. 51,59 Low uptake rates of telepsychiatry use and survey data suggest that many clinicians remain skeptical about this mode of care, 11,49,58,69,80,132 and negative biases remain a barrier at the health system leadership and clinician level. 8 In contrast to typically positive patient satisfaction with telemental health services, clinicians often report lower expectations about the value of telemental health and lower satisfaction.…”
Section: Clinician Acceptance/clinician As Gatekeepermentioning
confidence: 99%